Visual analysis of emerging topics and trends in contrast agent extravasation research in medical imaging: a bibliometric study using CiteSpace and VOSviewer - Yun Liu; Yonghai Dong; Wenfang Zhou; Juhong Yu (Frontiers in Medicine)
PurposeThis study presents a visualization of the global research dynamics on contrast agent extravasation in medical imaging using a knowledge map, revealing the research directions, emerging topics, trends, and frontiers in this field.MethodUsing CiteSpace and VOSviewer software with the Web of Science Core Collection database as the data source, a bibliometric analysis was conducted on relevant studies of contrast agent extravasation in medical imaging examinations. Analysis was performed on aspects such as yearly publication volume, country/institution distribution, authorship, co-citation documents, and keywords, leading to the creation of visualizations.ResultsA total of 4,635 articles were included in the study, with the first relevant research report appearing in 1950. The yearly publication and citation volumes have shown an overall increasing trend over the years. Research in this field was predominantly concentrated in the United States, accounting for approximately one-third of the global publication output. The University of California System was the top institution in terms of publication volume. The top five high-frequency keywords were “magnetic resonance imaging,” “computed tomography,” “management,” “diagnosis,” and “contrast agent.” Cluster analysis of keywords revealed three main clusters: “contrast,” “fluorescein angiography,” and “focused ultrasound,” showing good continuity over time. The keyword burst analysis identified that “gd dtpa” had the highest burst value of 20.51. The emergence of keywords shifted over time. At present, the keywords that are still emerging are “multimodal imaging,” “case report,” and “leakage.”ConclusionMore scholars are dedicating efforts to research on contrast agent extravasation in medical imaging. “Multimodal imaging” will be a key research focus in the foreseeable future. Contrast agent extravasation remains a substantial challenge with high research value in medical imaging.